Analysis of the Effect of Voltage and Zinc Plating Duration on Low Carbon Steel A36 by Electroplating Process on Corrosion Rate - Ari Wibawa Budi Santosa; Agil Arianda Alkhudry; Untung Budiarto; Eko Sasmito Hadi; Andi Trimulyono (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2024)
Corrosion is a significant issue in steel constructions, and zinc coating (electroplating) is one of the methods used to protect steel from corrosion. This research aims to analyze the effect of voltage and duration of zinc coating on low carbon steel A36 through the electroplating process on the corrosion rate and coating thickness. An experimental method was employed, varying the voltage (6, 8, and 10 Volts) and coating duration (10, 20, and 30 minutes) during the electroplating process using a ZnO solution. The corrosion rate was tested electrochemically in a 3.5% NaCl solution. The results showed a significant correlation between voltage, coating duration, corrosion rate, and coating thickness. Higher voltages and longer durations produced thicker zinc coatings and reduced the corrosion rate. The optimal conditions were found at 10 Volts for 30 minutes, producing a 160 (Mu)m thick coating and the lowest corrosion rate of 0.00318 mmpy. The minimal coating condition, 6 Volts for 10 minutes, resulted in a 30 (Mu)m thick coating and a corrosion rate of 0.050120 mmpy.